IMPROVING EMPLOYEE JOB SATISFACTION: DO TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE MATTER? - Aristana, I Nengah; Arsawan, I Wayan Edi; Wisnawa, I Made Bayu (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study aims to validate the determinants of employee job satisfaction in the hospitality industry. A quantitative approach with a questionnaire was used as a data collection tool that was distributed to 240 five-star hotel employees. The data were analyzed using SmartPLS 3.2.9. The findings prove that transformational leadership does not affect employee job satisfaction but positively influences organizational culture. Meanwhile, organizational culture fully mediates the relationship between transformational leadership and employee job satisfaction. This study has several limitations, namely, the bias of using self-assessment reports and the limited number of samples in the hotel industry in Bali. The practical implication is that leaders' success in building an organizational culture can be vital to increasing satisfaction. Thus, managers can better understand the relationship between variables and how the role of mediation is shown. In addition, it can provide more in-depth information as a reference for policy-making. Theoretically, this study contributes to the knowledge base in which the existing organizational culture significantly determines employee job satisfaction.JEL: A13, D23, D91.